2008
DOI: 10.2147/opth.s1067
|View full text |Cite
|
Sign up to set email alerts
|

Topical ophthalmic NSAIDs: a discussion with focus on nepafenac ophthalmic suspension

Abstract: The removal of diclofenac sodium ophthalmic solution as a viable pharmaceutical entity in September 1999 from the US market spurred considerable interest in the general safety and effectiveness of topical ophthalmic NSAIDs for treatment of anterior segment inflammation. In late 1999 the use of topical ocular NSAIDs declined in the US as a result of incidents involving corneal melts and toxicity surrounding use of generic diclofenac. However, since the removal of diclofenac sodium ophthalmic solution from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 43 publications
(81 reference statements)
0
53
0
2
Order By: Relevance
“…Corneal erosion has been labelled as an NSAID class effect, and was therefore targeted as an AE of special interest in the study. As such, exclusion criteria were added to prevent enrolment of patients with compromised corneas 23 24. One case of corneal erosion in the nepafenac group was assessed by the investigator as related to study treatment (out of two reported).…”
Section: Discussionmentioning
confidence: 99%
“…Corneal erosion has been labelled as an NSAID class effect, and was therefore targeted as an AE of special interest in the study. As such, exclusion criteria were added to prevent enrolment of patients with compromised corneas 23 24. One case of corneal erosion in the nepafenac group was assessed by the investigator as related to study treatment (out of two reported).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobic NSAIDs such as indomethacin, ibuprofen, and diclofenac, indicated for inflammatory disorders, are an excellent example to demonstrate the need for improved ocular delivery. Although, in-vitro studies have suggested their pharmacological effectiveness, studies involving animal models and patients generally fail to achieve sufficient therapeutic activity [5, 6]. Such failure is most likely due to insufficient retention and accumulation at the target site resulting in suboptimal therapeutic levels.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory process involves many mediators such as prostaglandin, leukotrienes, vascular endothelial growth factor and interleukins. Antiinflammatory effects of NSAIDs are mainly by inhibition of Cyclooxygenase (COX) activity which reduces prostaglandin production [14,15]. By blocking prostaglandin synthesis which is one of the inflammatory mediators, NSAIDS are shown to be effective in inhibiting the blood-retinal barrier breakdown thus reducing vascular hyperpermeability [11,13,16].…”
Section: Discussionmentioning
confidence: 99%